Benchmarking Efficiency Telecommunication Industries US and Major European Countries: A Stochastic Possibility Frontiers Approach - Georg Erber (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
Productivity growth and in particular the significant acceleration of productivity growth in the US economy in the second half of the 1990?s, raised high expectations that the massive investment in ICT-capital goods had finally had its impact on the whole US economy. Numerous growth accounting studies found that the large investments in the 1990?s were the key factor contributing to this development (see, e.g., OLINER & SICHEL, 2000; JORGENSON & STIROH, 2000; JORGENSON 2001, 2003; GORDON 2000A, 2000B; COUNCIL OF ECONOMIC ADVISORS, 2001). This new dynamism led – after two decades of debate about the persistent productivity slowdown since the mid-1970?s – to a catchword of a ?new economy?. Information processing via computers everywhere and the rapid global dissemination of data using digital communications over the Internet and new digital wireless networks were contributing in the make- as well as in the use-industries to a significant surge in US productivity growth.
Keywords: 330